Prestasi akademik mengikut gender - Zalizan Mohd Jelas,; Saemah Rahman,; Roselan Baki,; Jamil Ahmad, (penerbit ukm, 2005)
This article addresses gender differences in academic performance within the Malaysian education system. Secondary data on public examination results over a period of five years (1996-2000) were analysed and a questionnaire was administered on 3,000 secondary school students and 1,118 teachers. The student questionnaire explored students’ style of learning, their study skills and feelings toward teachers and school in general; whereas the teacher questionnaire explored teacher perceptions towards male and female students’ learning style,and their interpretation and implementation of the curriculum. National examination results at all levels (UPSR, PMR and SPM) in 1996-2000 shows that girls perform better than boys across almost all school subjects. The nature of these differences was examined and some of the underlying factors behind these differential achievements were discussed. It has been found that girls seem to do better on sustained tasks that require memorising unambiguous facts and rules while boys are more responsive to open-ended tasks, which are related to practical and realistic situations. Result of the study also shows that girls possess positive characteristics that contribute to better academic performance compared to boys. An analysis of the approaches towards creating a context for achievement of both girls and boys is offered, with a focus on pedagogical and socio-cultural strategies.